Pengaruh Financial Stability, Leverage Dan Karakteristik Komite Audit Terhadap Fraudulent Financial Reporting - Wening Sekar Astuti; Shinta Ningtiyas Nazar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of financial stability, leverage, and audit committee characteristics on fraudulent financial reporting. This research was conducted by analyzing the financial statements of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2021. The samples used in this study were 36 companies using purposive sampling technique. The data used in this study are secondary data in the form of financial statements from each company that has been sampled. The variables used in this study are Financial Stability (X1) as the first independent variable, leverage (X2) as the second independent variable, and audit committee characteristics (X3) proxied by an independent audit committee as the third independent variable and fraudulent financial reporting as the dependent variable. The panel data regression method is used as the research methodology in this study. The results showed that the best model was the Fixed Effect Model (FEM). The results of this study indicate that financial stability partially has no effect on fraudulent financial reporting, leverage has a significant positive effect on fraudulent financial reporting and audit committee characteristics have a significant negative effect on fraudulent financial reporting. Keywords: Financial Stability, Leverage, audit committee characteristics, fraudulent financial reporting.